Essentials of Understanding Psychology - Feldman, Robert S., 1947- (Robert Stephen) (New York : McGraw-Hill, 2015)
Do your teaching materials treat them that way? From an adaptive diagnostic tool that provides a GPS for learning to a reader-friendly modular organisation, this book ensures that every student gains a better understanding of psychology.
Includes bibliographical references and index
Keywords: Psychology -- Textbooks; Psychology; Textbooks